MALONDIALDEHYDE LEVELS AND ACTIVITY OF SUPEROXIDE DISMUTASE IN THE ORAL FLUID OF PATIENTS WITH CHRONIC GENERALIZED PERIODONTITIS - Khudiakova, M.B. (World of Medicine and Biology, 2015)
The research in question demonstrates pathogenetic role of abnormal processes of lipid peroxidation and antioxidant defense in the oral fluid in their connection with clinical change in development of chronic generalized periodontitis of I-II degree of severity. High therapeutic efficiency of the lipoflavon was shown to be determined by antioxidant, membranotropic, anti-inflammatory effects.
Keywords: malondialdehyde; lipid peroxidation; superoxide dismutase; antioxidant activity; chronic generalized periodontitis; pathogenesis; lipoflavon